Why do people live in disaster-prone char regions? Perspectives from Assam, India - Mrinal Saikia; Ratul Mahanta (Discover Global Society)
Abstract People residing in the char regions of Assam are among the most vulnerable in the state, and particularly susceptible to multiple disasters such as floods, storms, and land erosion. Despite the existing vulnerabilities and widespread poverty, people continue to live in these areas. Our research aims to investigate why people continue to reside in these areas in such conditions and explore the feasibility of relocation as a possible solution to catastrophe risk mitigation, considering people's perceptions of living in these locations. This study uses a mixed method’s approach to achieve its objectives, based on primary data, collected through a household survey and focus group discussions. A total of 394 char residents from four districts of Assam participated in data collection. The Contingent Valuation Method (CVM) has been applied to understand residents' living preferences. Additionally, we used regression models to determine the factors influencing char residents' preference for living in these vulnerable areas. Our findings reveal that while most people prefer to live in the char areas, the risks of multiple disasters are driving some to consider leaving, exacerbated by infrastructure bottlenecks. However, char dwellers do not view relocation as a desirable solution. Alternatively, improving infrastructure and reducing disaster risks could lead to higher-levels of development and satisfaction for char residents.